Causes and Prevention of Emitter Plugging In Microirrigation Systems - D. Z. Haman (EDIS)
Microirrigation systems have gained popularity in horticultural crop cultivation due to their ability to deliver water and nutrients directly to the plant's root zone. These systems utilize a network of pipes to distribute water to emitters, which discharge it in various forms such as droplets, small streams, or mini-sprayers. Over the past two decades, microirrigation has emerged as a preferred method for both irrigation and freeze protection in trees and horticultural crops. When managed effectively, microirrigation offers several advantages, including comparable water application uniformity, improved water use efficiency, minimized deep percolation and runoff with proper scheduling, efficient delivery of fertilizers and chemicals through fertigation and chemigation, and the ability to irrigate land too steep for other irrigation methods. However, one significant challenge associated with microirrigation systems is the plugging of emitters, which can severely impact water application uniformity. Addressing emitter plugging remains a critical area for further research and system optimization in microirrigation practices.